The rubber formulary - Ciullo, Peter A., 1954- (PDL handbook series., 1999)
Rubber products discussed include seals and gaskets for windows, pressure and vacuum hoses for automotive and aerospace applications, bottle stoppers for medical and pharmaceutical products, center cores for all types of balls, belts for tools and machinery, shock and vibration absorbers for everything from motor mounts to sky scrapers, insulation for blankets, and even large film coatings for roofing applications.